2002
DOI: 10.1046/j.1563-2563.2002.02072.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sentinel Lymph Nodes in Breast Cancer by Lymphoscintigraphy and Gamma Probe Guidance: Dependence on Route of Injection and Tumour Location

Abstract: Background: Sentinel lymph node detection with radiocolloids is confronted with the same problem as the blue dye (BL) method: Even now there is no standardized procedure as regards the application method, the amount of radioactivity and injected volume of the radiocolloid (RC). Therefore, our aim was to find out the most reliable application method and to evaluate a possible tumour-site dependence of detectability. Methods: Until 1 November 2001, 1567 patients with primarily diagnosed breast cancer and SNB wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…For reliably detecting the sentinel nodes, different blue dyes (isosulfan blue, patent blue) were tested and recommended either alone or in combination with radioactively labelled colloids (6, 17, 23, 28, 42, 52, 57). Studies in functional anatomy suggested various modes of application, i. e. peritumoral (24), intradermal and subcutaneous (49, 81) or peri‐ and subareolar (40, 54, 60, 71).…”
Section: Lymphatic Mappingmentioning
confidence: 99%
“…For reliably detecting the sentinel nodes, different blue dyes (isosulfan blue, patent blue) were tested and recommended either alone or in combination with radioactively labelled colloids (6, 17, 23, 28, 42, 52, 57). Studies in functional anatomy suggested various modes of application, i. e. peritumoral (24), intradermal and subcutaneous (49, 81) or peri‐ and subareolar (40, 54, 60, 71).…”
Section: Lymphatic Mappingmentioning
confidence: 99%